Propulsive force of upper limbs and its relationship to swim velocity in the butterfly stroke - Morais, J.; Barbosa, T. M.; Lopes, V. P.; Marques, M. C; Almeida Marinho, D. (International Journal of Sports Medicine, 2021)
The aims of this study were to: (1) verify the sex effect; (2) assess upper limb asymmetry in anthropometrics and propulsive force variables; and (3) identify the main determinants of butterfly swim velocity based on a set of anthropometrics, kinematics, and propulsive force variables. Twenty swimmers (10 males: 15.40±0.30 years; 10 females: 14.43±0.23 years) at the national level were recruited for analysis. A set of anthropometrics, kinematics, and propulsive force variables were measured. Overall, a significant sex effect was verified (p=0.05). Non-significant differences between upper-limbs were noted for males and females in all variables, except for the dF in males (t=-2.66, p=0.026, d=0.66). Stroke frequency presented the highest contribution, where a one unit increase in the stroke frequency imposed an increase of 0.375 m·s-1 (95CI: 0.105;0.645, p=0.010) in the swim velocity. The swim velocity was predicted by the mean propulsive force, intra-cyclic variation of the swim velocity, and stroke frequency. Overall, swimmers exhibit non-significant differences in the variables assessed. Swim velocity in the butterfly stroke was determined by an interaction of propulsive force and kinematic variables in young swimmers.